Alteration of intestinal microflora by the intake of millet porridge improves gastrointestinal motility - Chen, Ying; Zhang, Rong; Xu, Jialiang; Ren, Qing (Frontiers in Nutrition, 2022)
Foxtail millet (Setaria italica) has a long history of treating gastrointestinal ailments in China; however, little is known about the functional mechanism driving its therapeutic effects. The primary edible form of millet is porridge. This study investigates the effects of millet porridge on diphenoxylate-induced constipation and intestinal microflora in mice. Fifty mice were randomly divided into five groups: normal control group, constipation model group, and low-dose, medium-dose, and high-dose millet porridge groups. After 14 days of millet porridge gavage, constipation was induced and measured. The results showed that millet porridge prevented constipation by increasing the water content of feces, shortened the time of the first melena defecation, promoted gastric emptying, and improved the rate of gastrointestinal propulsion. Millet porridge also dose-dependently increased levels of Bifidobacterium and Lactobacillus and decreased levels of E. coli, Enterococcus, and Bacteroides in the intestine. These results show that millet porridge could accelerate intestinal motility and change the proportions of intestinal flora and that it has a potent prebiotic effect.